Antioxidative properties and macrochemical composition of five commercial mungbean varieties in Australia. Issue 1 (12th January 2020) - Johnson, Joel; Collins, Tania; Power, Aoife; Chandra, Shaneel; Skylas, Daniel; Portman, Drew; Panozzo, Joe; Blanchard, Christopher; Naiker, Mani
Abstract: Mungbeans are growing in popularity among Australian consumers, driven by their beneficial nutritional and phytochemical composition. However, data on the antioxidative, mineral, and phytochemical content of Australian mungbeans at the point of consumer purchase remains scarce. Here, five commercial mungbean samples were analysed for total antioxidant capacity, total phenolics, and total monomeric anthocyanins. Attenuated total reflectance midinfrared spectroscopy was utilised as a rapid and reliable method of obtaining information about the macrochemical composition of the mungbean hulls. Total antioxidant capacity ranged from 170 to 570 mg Trolox equivalents per 100 g, total phenolic content from 130 to 240 mg gallic acid equivalents per 100 g, and anthocyanin content from 10 to 40 mg cyanidin‐3‐glucoside equivalents per 100 g. There was a significant difference between varieties in all measures of antioxidant, phenolic and anthocyanin contents. Using principal component analysis, the midinfrared spectra for the five mungbean varieties could be isolated, highlighting the differences in their phytochemical composition. In general, whole Australian mungbeans appear to have the highest antioxidant, phenolic, and anthocyanin contents. Midinfrared spectroscopy appears to be a valuable method of obtaining and comparing the macrochemical composition of mungbeans. This technology is likely to be of increasing use in the future.